Security and Special Operations - Murphy, C. author. aut Link
XII, 253 p.
Keywords: This volume offers the first comprehensive history of the Security Section of the Special Operations Executive and its relationship with MI5 during the Second World War. The book makes extensive use of recently declassified files in order to examine the development of liaison between the two organizations.